The serial dilution culture-most probable number assay to estimate phytoplankton concentrations in ballast water: comments and improvements - Peperzak, Louis (Frontiers in Marine Science, 2024)
In ecology, the enumeration of living aquatic unicellular protists is a century-old complicated task. The organisms are small, perhaps motile, and if they are non-motile their vitality is hard to gauge. A respectable technique still in use today is the Serial Dilution Culture-Most Probable Number (MPN) assay that determines the total viable phytoplankton concentration from the highest sample dilutions that exhibit chlorophyll-fluorescence after incubation. However, 99% of extant phytoplankton species have not been shown to grow in MPN tubes (false-negatives) and in ballast water applications, 10-50 µm species can be outcompeted by <10 µm autotrophs in abundance, biomass, and chlorophyll-fluorescence (false-positives). In addition, it is shown that after microscopic identification, contrary to established practice, the concentration of individual species or species-groups (10-50 µm) cannot be derived from standard MPN tables. Examples of a corrected derivation are given for simple (2-3 species) assemblages, but this correction becomes increasingly difficult in more complex mixtures. The MPN assay should not be used as a quantitative method in ecological studies or in applications such as ballast water testing.